Erysipèle du membre inférieur: étude de 400 cas [Erysipelas of the lower limb: study of 400 cases] - Amina Aounallah; Ines Lahouel; Marouen Belkahla; Mouna Korbi; Amel Mbazaa; Wafa Saidi; Sana Mokni; Lobna Boussofara; Rima Gammoudi; Najet Ghariani; Mohamed Denguezli; Colandane Belajouza; et al. (Our Dermatology Online, 2017)
Introduction: Erysipelas is an acute, non-necrotizing dermo-hypodermitis of predominantly streptococcal origin. Objective: To clarify the epidemiological and evolutionary features of the lower limb erysipelas through a hospital series. Materiels and Methods: We retrospectively analyzed all cases of lower limb erysipelas hospitalized in the Department of Dermatology of the Farhat Hached Hospital of Sousse between January 2000 and December 2015 (10 years). Results: Four hundred cases of erysipelas of the lower limb were recorded. The mean age of the patients was 55.82 years. The sex ratio was 1.51. The main predisposing factors were sedentarity, diabetes and obesity. In 96.75% of cases, entry lesion, like mycoses or traumatic injuries was noted. Clinically, a classic presentation of erysipelas was described in all cases. Erysipela was unilateral in 96% of cases. Treatment was based on intravenous penicillin G in 86.5% of cases, on an average of 9.75 days. The evolution was favorable in 83.25% of cases. Antibioprophylaxis was prescribed in 38% of cases. Loco-regional and general complications were noted in 10.25% of cases. Three patients died. Late complications were dominated by relapses and persistence of sequelled lymphedema. RÉSUMÉ Introduction: L'érysipèle est une dermo-hypodermite aigue, non nécrosante, d'origine principalement streptococcique. Objectif: préciser les particularités épidémio-cliniques et évolutives de l'Erysipèle du membre inferieur à travers une série hospitalière. Matériel et Méthodes: Nous avons rétrospectivement analysé tous les cas d'érysipèle du membre inférieur hospitalisés dans le service de dermatologie de l'hôpital Farhat Hached de Sousse entre janvier 2000 et décembre 2015 (10 ans). Résultats: Quatre cents cas d'érysipèle du membre inférieur ont été recensés. L'âge moyen des patients était de 55.82 ans. Le sexe ratio était de 1.51. Les principaux facteurs favorisants étaient : la sédentarité, le diabète et la surcharge pondérale. Une porte d'entrée à type d'intertrigo interorteil ou de plaie traumatique était notée dans 96.75% des cas. Cliniquement, un tableau typique d'érysipèle était décrit dans tous les cas. L'atteinte était unilatérale dans 96% des cas. Le traitement était à base de pénicilline G par voie intraveineuse dans 86,5% des cas pendant en moyenne 9.75 jours. L'évolution était favorable dans 83.25% des cas. Une antibioprophylaxie était prescrite chez 38% des cas. Les complications loco-régionales et générales précoces étaient notées dans 10.25% des cas. Trois patients étaient décedés. Les complications tardives étaient dominées par les récidives et la persistance d'un lymphoedème séquellaire.